Flexural strength of modified and unmodified acrylic denture base material after different processing techniques - Kiran, Aisha; Amin, Faiza; Mahmood, Syed Junaid; Ali, Arif (Journal of Ayub Medical College Abbottabad, 2021)
Objective: To determine and compare the effect of different processing techniques on flexural strength of modified and unmodified denture base acrylic resin. Air circulating oven is introduced for the first time in this study and its efficacy was also compared with other conventional processing techniques. Materials and Methods: In this study total number of 114 rectangular specimens were fabricated by conventional heat cured acrylic (Stellon QC 20, Dentsply) for Group A (n=57), and rubber reinforced acrylic resin (High impact, Meadway) for Group B (n=57). Three equipments including water bath, dry oven and air circulating oven were utilized for processing specimens individually. Each sub-group of processing techniques (n=19), were tested for flexural strength through a three point bending test by a universal testing machine. The statistical analysis initiated with descriptive analysis followed by independent t test for mean comparison of flexural strength of all three processing techniques among both testing group. 1-way ANOVA and 2-way ANOVA followed by scheffe post hoc test were also applied. P-value of 0.05 or less was considered as significant. Results: Statically significant P-Value <0.001 was found in response of flexural strength in all processing techniques (water bath, dry oven, air circulating oven) of both testing groups. Water bath processing demonstrated highest flexural strength values in both denture base material used in this study. The unit used for flexural strength was MPa. Conclusion: This study manifested highest flexural strength in conventional and rubber reinforced heat cure samples when processed through water bath. Air circulating oven also presented acceptable flexural strength in conventional heat cure acrylic resin specimens when compared with other techniques.